2015
DOI: 10.1038/jid.2015.159
|View full text |Cite
|
Sign up to set email alerts
|

RIPping the Skin Apart: Necroptosis Signaling in Toxic Epidermal Necrolysis

Abstract: Toxic epidermal necrolysis (TEN) is a rare but potentially fatal drug hypersensitivity reaction. Although a number of pathophysiological hints have been identified over the past decade, details of the effector mechanisms within the skin remain obscure. A novel study by Kim et al. now sheds light on its pathophysiology. The investigators demonstrate convincingly that receptor-interacting kinase 3 (RIPK3) levels are upregulated substantially in the lesional skin of patients with TEN and that this is followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…It is well known that keratinocyte death in SJS/TEN results from the action of cytotoxic cells or soluble factors such as soluble FasL or granulysin (1,2). Classical apoptosis and the more recently described programmed necrosis (necroptosis) have been proposed as relevant cell death pathways responsible for the extensive keratinocyte death seen in SJS/TEN (47). Whether other forms of cell death-pyroptosis, ferroptosis, or autophagy-were involved in the pathogenesis of SJS/TEN remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that keratinocyte death in SJS/TEN results from the action of cytotoxic cells or soluble factors such as soluble FasL or granulysin (1,2). Classical apoptosis and the more recently described programmed necrosis (necroptosis) have been proposed as relevant cell death pathways responsible for the extensive keratinocyte death seen in SJS/TEN (47). Whether other forms of cell death-pyroptosis, ferroptosis, or autophagy-were involved in the pathogenesis of SJS/TEN remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…RIP3-dependent phosphorylation leads to a potent mechanism of inflammatory disease pathogenesis via activation of pore-forming proteins and disruption of membrane integrity. 13 Programmed necrosis mediated by tumor necrosis factor (TNF)-α and nitric oxide (NO) is potentiated by high RIP levels; TNF-alpha, NO, and RIP3 are found in abundance in TEN. 14 Importantly, dabrafenib directly inhibits RIP3 kinase activity, in addition to TNF-alpha and NO-induced necroptosis of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, murine genetic studies have started to document how unrestrained MLKL-dependent necroptotic signaling can result in embryonic lethality 3 and cause liver inflammation 25 . In addition, the development of phospho-specific MLKL antibodies as markers of activated MLKL have shown that necroptosis is likely to occur in diseases such as toxic epidermal necrolysis 26 , 27 , drug-induced liver injury 28 , and pathogen infection 21 . Cancer cell lines have also been observed to suppress RIPK3 expression 29 , which in some circumstances has been attributed to DNA methylation 30 .…”
Section: Introductionmentioning
confidence: 99%